2014
DOI: 10.1186/s12967-014-0318-7
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic potential of human embryonic stem cell transplantation in patients with cerebral palsy

Abstract: BackgroundThe present study evaluated the efficacy and safety of human embryonic stem cell (hESC) therapy in patients with CP.Materials and methodsThis analysis included patients (30 days-18 yr) with documented diagnosis of CP. The study consisted of four treatment phases (T1, T2, T3, T4) separated by gap phases. Efficacy of hESC therapy was evaluated based on Gross Motor Function Classification Scores Expanded and Revised (GMFCS-E & R; 1-good to 5-bad).ResultsNinety one patients were included and all received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 32 publications
1
76
0
Order By: Relevance
“…Other changes includes improved urinary bladder control in Case I, improved overall stamina and coordination in Case II and improved spine curvature in Case III. Our finding that the hESCs are capable of treating FRDA is supported by our previous studies, where hESCs have successfully treated the patients with cerebral palsy [12]. Human embryonic stem cells might have the potential to treat patients with neurodegenerative diseases such as cerebral palsy, Friedreich's ataxia, etc.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Other changes includes improved urinary bladder control in Case I, improved overall stamina and coordination in Case II and improved spine curvature in Case III. Our finding that the hESCs are capable of treating FRDA is supported by our previous studies, where hESCs have successfully treated the patients with cerebral palsy [12]. Human embryonic stem cells might have the potential to treat patients with neurodegenerative diseases such as cerebral palsy, Friedreich's ataxia, etc.…”
Section: Discussionsupporting
confidence: 82%
“…In our previous studies we have shown the improvement in patient's condition who were suffering from cerebral palsy and cortical visual impairment after hESCs therapy [12,13]. Herein, I report three cases of FRDA patients who were treated with hESCs therapy.…”
Section: Shroff 262mentioning
confidence: 87%
See 1 more Smart Citation
“…[35][36][37][38] The differentiation of embryonic stem cells has been explained and discussed in our previous paper. 39 Until now, we have used this cell line in > 1400 patients with various incurable conditions with remarkable results.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cells that have been explored in animal models for the treatment of AMD include embryonic stem cells (ESCs) and human induced pluripotent stem cells (iPSCs) and mesenchymal stem cells (MSCs) [2,6]. In our previous studies we have shown the improvement in the patient's condition suffering from cerebral palsy, cortical visual impairment (CVI), Lyme's disease, spinocerebellar ataxia, Friedreich's ataxia and spinal cord injury after human embryonic stem cells (hESCs) therapy [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%